Occurrence of aflatoxins in selected processed foods from Pakistan - Mushtaq, Muhammad; Sultana, Bushra; Anwar, Farooq; Khan, Muhammad Zargham; Ashrafuzzaman, Muhammad (MDPI, 2012)
A total of 125 (ready to eat) processed food samples (70 intended for infant and 55 for adult intake) belonging to 20 different food categories were analyzed for aflatoxins contamination using Reverse Phase High Performance Liquid Chromatography (RP-HPLC) with fluorescent detection. A solvent mixture of acetonitrile-water was used for the extraction followed by immunoaffinity clean-up to enhance sensitivity of the method. The limit of detection (LOD) (0.01–0.02 ng·g−1) and limit of quantification (LOQ) (0.02 ng·g−1) was established for aflatoxins based on signal to noise ratio of 3:1 and 10:1, respectively. Of the processed food samples tested, 38% were contaminated with four types of aflatoxins, i.e., AFB1 (0.02–1.24 μg·kg−1), AFB2 (0.02–0.37 μg·kg−1), AFG1 (0.25–2.7 μg·kg−1) and AFG2 (0.21–1.3 μg·kg−1). In addition, the results showed that 21% of the processed foods intended for infants contained AFB1 levels higher than the European Union permissible limits (0.1 μg·kg−1), while all of those intended for adult consumption had aflatoxin contamination levels within the permitted limits.